タセイブン ノウド ソウカン ニヨル ナンキョク スイケイ ノ カイセキ - 綿抜, 邦彦; ワタヌキ, クニヒコ; WATANUKI, Kunihiko (国立極地研究所, 1977)
P(論文) 南極湖沼水の相互関係およびその起源を解析するために,多成分濃度相関マトリックス法を適用した.この方法は成分相互間の相対比を用いてマトリックスを作る方法で,相互関係を強調して取り扱える点に特色がある.その結果,昭和オアシスのぬるめ池は,海水がとりこまれて比較的変化の少ない湖沼であること,舟底池は硫酸塩の生成のため,海水からの進化の多少あること,マクマード・オアシスのパンダ湖の湖底水は,著しく進化した湖沼水であることが推定された.また,ボニー湖の東西の部分は表層水では相互の関係が深いが,湖底水では相互関係があまり認められず,もし海水が起源とすれば,西側が源であり東側はこれから派生したものと推定される.このほか昭和オアシスの淡水湖は,ほぼ同じような過程で生成したとみるべきこと,マクマード・オアシスのオニックス池は,氷河融氷水で函養されていることなどが明らかとなった. Correlation among the water systems in Antarctica is analyzed by the correlation concentration matrix method. The method is a technique of matching the ratios of the elemental concentration of the sample with the equivalent ratios of other samples. The concentration ratios {x_ } for the sample are formed by dividing the concentration of each element by that of the other element. {y_ (kl)} is obtained by dividing each element of the concentration matrix for sample k by corresponding element of sample l. z_<kl> is a correlation number, that is a proportion of the matrix element {y_ (kl)} that meets the matching criterion. z_<kl> has a value between 0 and 1. Using correlation numbers we can find generic relationship among Antarctic water systems. Some of examples are shown as follows. High correlation number is obtained between the water of Lake Nurume and the sea water. It suggests that the water of Lake Nurume was originated from sea water and has not been much changed. Also high correlation number is obtained between the Onyx Pond water and the inflow water of Lake Vanda. It means that the water of Onyx Pond is supplied from the melt water of glacier of the area. The data of correlation revealed that the water of the east lobe of Lake Bonney is different in origin from the water of the west lobe of the lake. departmental bulletin paper